Age, Empowerment and TikTok: Redefining the Image of Older Women in the Digital Space - Castro-Bernardini, María José (2024)
This study analyzes the representation and participation of older women on TikTok, an emerging social platform. Through a thorough content analysis of selected videos and profiles, it addresses how these women are challenging conventional media representations. The research details their participation in activities such as dances and challenges, which contradicts traditional perceptions of obsolescence and conformity to domestic roles. The findings reveal a meaningful and creative participation of older women, redefining their image in the digital context. This shift not only disproves common stereotypes, but also suggests a change in the societal perception of this demographic. This study contributes to a deeper understanding of the agency and vitality of older women in social networks, offering valuable insights for future research in advertising communication and media studies.